Terrestrial Dissolved Organic Matter Mobilized From Eroding Permafrost Controls Microbial Community Composition and Growth in Arctic Coastal Zones - Bruhn, Anders Dalhoff; Stedmon, Colin A.; Comte, Jérôme; Matsuoka, Atsushi; Speetjens, Niek Jesse; Tanski, George; Vonk, Jorien E.; Sjöstedt, Johanna (Frontiers in Earth Science, 2021)
Climate warming is accelerating erosion along permafrost-dominated Arctic coasts. This results in the additional supply of organic matter (OM) and nutrients into the coastal zone. In this study we investigate the impact of coastal erosion on the marine microbial community composition and growth rates in the coastal Beaufort Sea. Dissolved organic matter (DOM) derived from three representative glacial deposit types (fluvial, lacustrine, and moraine) along the Yukon coastal plain, Canada, were used as substrate to cultivate marine bacteria using a chemostat setup. Our results show that DOM composition (inferred from UV-Visible spectroscopy) and biodegradability (inferred from DOC concentration, bacterial production and respiration) significantly differ between the three glacial deposit types. DOM derived from fluvial and moraine types show clear terrestrial characteristics with low aromaticity (Sr: 0.63 ± 0.02 and SUVA254: 1.65 ± 0.06 L mg C−1 m−1 & Sr: 0.68 ± 0.01 and SUVA254: 1.17 ± 0.06 L mg C−1 m−1, respectively) compared to the lacustrine soil type (Sr: 0.71 ± 0.02 and SUVA254: 2.15 ± 0.05 L mg C−1 m−1). The difference in composition of DOM leads to the development of three different microbial communities. Whereas Alphaproteobacteria dominate in fluvial and lacustrine deposit types (67 and 87% relative abundance, respectively), Gammaproteobacteria is the most abundant class for moraine deposit type (88% relative abundance). Bacterial growth efficiency (BGE) is 66% for DOM from moraine deposit type, while 13 and 28% for DOM from fluvial and lacustrine deposit types, respectively. The three microbial communities therefore differ strongly in their net effect on DOM utilization depending on the eroded landscape type. The high BGE value for moraine-derived DOM is probably caused by a larger proportion of labile colorless DOM. These results indicate that the substrate controls marine microbial community composition and activities in coastal waters. This suggests that biogeochemical changes in the Arctic coastal zone will depend on the DOM character of adjacent deposit types, which determine the speed and extent of DOM mineralization and thereby carbon channeling into the microbial food web. We conclude that marine microbes strongly respond to the input of terrestrial DOM released by coastal erosion and that the landscape type differently influence marine microbes.